The potential of microalgae for wastewater nutrient removal combined with polyhydroxybutyrate (PHB) production - Oanh Doan, Thi; Thuy Duong, Thi; Anh Pham, Le; Hang Hoang, Thi Thu; Trung Nguyen, Thanh; Mai Vu, Thi; Thao Nguyen, Thi Phuong; Hanh Nguyen, Thi Hong; Quynh Chu, Thi Ngoc (Vietnam Journal of Earth Sciences, 2025)
Poor management of domestic wastewater and dependence on synthetic plastics have been placing a heavy burden on the natural environment, endangering both the ecosystem and human well-being. Microalgae technology has demonstrated enormous potential in simultaneously addressing both problems through wastewater remediation and nutrient recovery, while also facilitating the production of bioplastics. This study evaluated the growth performance, polyhydroxybutyrate (PHB) production, and the ability of four microalgae strains, including Scenedesmus sp., to treat domestic wastewater. SCE, Chlorella sp. HB, Chlorella sp. CNK, and Chlorella sp. CNA, cultivated in the standard artificial medium (Blue Green-11 - BG11), the standard artificial medium (BG11) with sodium acetate, and the real domestic wastewater, and aerated at an aeration rate of 1.2 v v-1 m-1 for 10 hours/day, at temperature 25°C, light intensity of 5 klux, a light: dark cycle of 10 hours: 14 hours for 12 test days. After 12 experimental days, the study results demonstrated that four microalgae achieved their highest biomass productivities and PHB contents in domestic wastewater, ranging between 7.0±0.4 and 25.7±0.5 mg L-1 d-1, and between 6.3±0.2 and 13.0±0.3% by weight, respectively. The addition of organic carbon (sodium acetate) to the standard medium could increase the growth and PHB accumulation capacity of microalgae, particularly in their mixotrophic growth. The microalgae also demonstrated good adaptability in domestic wastewater, achieving high efficiencies, with COD removal ranging from 53.6±4.7 to 78.1±1.1%, TN removal from 56.6±2.6 to 84.5±1.5%, and TP removal from 43.2±11.0 to 70.0±4.2%. Notably, the removal of nitrogen and phosphorus was primarily due to the assimilation of microalgae, further confirming their potential in nutrient recovery from wastewater. The two microalgae that performed the best were Scenedesmus sp. SCE and Chlorella sp. HB, with the estimated PHB productivities of 2.5±0.1 and 3.3±0.1 mg L-1 d-1, respectively. Future studies should focus on optimizing operational conditions to enhance performance, particularly in larger-scale cultivation systems.